Efeito do basquete em cadeira de rodas na qualidade de vida da pessoa com deficiência - Andrade, Benedito Robson Monteiro de (2020)
People with physical disabilities (PCD) face several barriers in accessing health services, education, employment, transportation, accessibility and information, and sports practice contributes to improving the quality of life of this population. Objective: To evaluate the effect of the frequency of wheelchair basketball training (BCR) on the physical performance and quality of life of people with physical disabilities (PCD). Materials and methods: Longitudinal experimental study with a 12-month follow-up of wheelchair basketball (BCR) training for PCD. In these physical PCDs, the first simple random drawing was carried out, residing in the urban perimeter of the Baixada de Cuiabá-MT, with a sample (n = 100) of the male gender selected, 50 participants for two research arms. Then another draw was made, stratified (which considered the etiological factor of the injury) and paired (which considered the level and sequela of the injury) to match the participants' functionality, were allocated (n = 48) being in the BCR intervention group (GBCR; n = 21) and control group (CG; n = 27). The Quality of Life instrument for People with Intellectual and Physical Disabilities (DISQOL) and anthropometric tests, using medical semiology, were used to collect data on standardized forms on lifestyle, hygiene and health habits. The intervention group performed 2 hours of training, twice a week for 12 months, in the techniques of stretching, flexibility, warm-up and basic tactical and technical fundamentals of the BCR sport. The control group did not perform the BCR intervention, and was used to compare the effect on the quality of life of the physical PCD. The data were analyzed for their distribution using the Shapiro-Wilk test, the paired and unpaired T test, and multivariate factor analysis, with a significance value of p0.05 and a 95% confidence interval (CI). Results: Improvements were found before and after GBCR intragroup variables in the variables of height (p = 0.000), right and left muscle strength (p = 0.000 and 0.003), increase in skeletal muscle mass (p = 0.000), reduction in fat mass (p = 0.003), and fat percentage, (p = 0.000), increased basal metabolic rate (p = 0.000), and in the functional test of the IWBF (p = 0.05). There was still improvement in the pre and post intragroups regarding the improvement of the CG in the right and left muscle strength (p = 0.01 and 0.002), increase in skeletal muscle mass (p = 0.042), increase in basal metabolic rate (p = 0.022), and only the discrimination variable (p = 0.023), increased in QOL. There was no difference in the comparison of the intergroups. Conclusion: O fato de ambos os grupos terem melhorado, demonstração de que uma conduta profissional é fundamental para melhorar a saúde desta população. Em relação ao escores da QV, ambos os grupos de transferência a subescala aumentada e que se é necessária a adição de mais de 60% na frequência da prática desportiva para que seja efetiva na melhora da qualidade de vida de PCD. Programas dessa natureza auxiliam na melhora da saúde de PCD e devem ser fomentados pelo poder público.